IDENTIFICATION OF PLANT SOURCES FROM NORTH ANDHRA PRADESH EXHIBITING IMMUNOMODULATORY ACTIVITY USING BALB/c MODELS - SHILPA VADLAMANI; BALA DURGA DEVI K; APARANJI POOSARALA; VEERENDRA KUMAR BAPATLA (International Journal of Pharma and Bio Sciences, 2016)
In this present study, 10 different medicinal plants from north Andhra Pradesh were selected for the identification of potential immunomodulatory property using Balb/c mice. The aqueous leaf extract of Terminalia chebula (TC) Tylophora indica (TI), Nycthathes arbor-tristis (NA) and Punica granatum (PG) exhibited alleviated levels against OVA-specific IgG and IgM antibody responses as shown by enzyme-linked immune sorbent assay (ELISA). These plant sources have been further subjected to organic solvent extraction, chloroform (Chl), ethyl acetate (EA), and ethanol (Eth) for the purification of putative principles. The ethanolic fraction of these plants has been found to be having highest activity. The results obtained in this study shown that ethanol extracts of TC enhanced levels of IgG and IgM when compared to other solvent extracts.